Can green credit enhance the competitiveness of commercial banks? Evidence from China - Sun, Ning; Liu, Jun; Wang, Junli (Frontiers in Applied Mathematics and Statistics, 2025)
How to better promote green credit is the focus of commercial banks’ development concerns. This paper studies the impact of green credit implementation on the competitiveness of commercial banks and is based on the panel data of 12 Chinese commercial banks from 2011 to 2020. It looks at 8 research indicators, such as green credit ratio. The generalized method of moments (GMM) method is used for regression. The empirical study shows that the implementation of green credit has a certain positive effect in the short term, but the effect is quite small, about 0.0032, 0.0012, 1.4857 and 0.4028. The reason may be the pressure to concentrate on short-term operational performance and the lack of drive commercial banks display in fulfilling their social responsibility. As a result, commercial banks have often failed to timely and effectively carry out green credit business in line with their own development status. However, when relevant control variables are introduced, including gross domestic product (GDP) of total assets, non-performing loan ratio and GDP growth rate, the results show that if the commercial banks implement green credit, they can effectively improve their return on total assets. When the relationship between the control variables is considered, the promotion effect is even more obvious, which proves that the implementation of green credit can promote competitiveness among China’s commercial banks in terms of business performance.